Diagnosis Prenatal dan Penatalaksanaan Omfalokel - Hasna Hamidah (MAJORITY, 2020)
Omfalocele is a congenital defect in the presence of herniation of part of the intra-abdominal contents through the umbilical ring that opens into the base of the umbilical cord on the abdominal wall with incidence rate is 1 per 3.000–5.000 during pregnancy, decreasing to 2,5–4 per 10.000 for live births. The survival rate of isolated omphalocele is as high as 96%, but the percentage drops significantly in the presence of associated anomalies or an abnormal karyotype. The complexity of the defect became challenging. Knowledge about the defect will improve prenatal diagnosis which is crucial for delivery management including timing and route of delivery. Addition assessment is also done to determine whether there is associated anomalies that show severity and determine postnatal prognosis. The recommended labor time is aterm. The recommended route of delivery is depend on defect size, section caesarea is indicated in the setting of a giant omphalocele. Neonatal management includes delivery in tertiary health facilities and management of postnatal surgery namely primary closure, staged delayed with silo bag and prosthetic patch, and conservative management with topical agents.